Parahyba masculina feminina neutra: Cinema (in) direto, super 8, gênero e sexualidade (Paraíba, 1979-1986) - Silva, Laércio Teodoro da (2012)
The present study draws upon the Super 8 mm cinematographic production in the State of Paraíba, Brazil, from 1979 – year in which the documentary Gadanho, by Pedro Nunes and João de Lima, was released – to 1986. The study analyzes the cinematographic experiences from their dialogs with the Brazilian production in the 1960’s and 1970’s, taking also into account the local scenario, which found a field marked by traditions which can be traced back to the 1960’s, when the documentary Aruanda (1960), by Linduarte Noronha, was released and became a marker of how cinema should be thought and made. The focus is on movies which tackle gender representations and expressions of sexuality. The analysis considers their making of process and their representations of femininity and masculinity, which criticize stereotypes of woman and of Brazilian Northeastern man, mainly, man from the State of Paraíba. The films are committed to a visibility policy, aiming mainly at the deconstruction of the homosexual character, raising new issues on practices and on representations of sexuality. Targeting at comprehending the process of circulation of such films, the spaces where they were displayed, such as the Federal University of Paraíba, cineclubs and independent film festivals were questioned. As a consequence, the following aspects were problematized too: the diverse interpretations and the wars of representations, not only in the theme of the films, but in the Super 8 films themselves, and, the process of affirmation of this production as a cultural object in the film field.